2011
DOI: 10.1111/j.1440-1681.2011.05496.x
|View full text |Cite
|
Sign up to set email alerts
|

Implant‐induced intraperitoneal inflammatory angiogenesis is attenuated by fluvastatin

Abstract: 1. Statins, 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMG-CoA) inhibitors, exert anti-inflammatory, anti-oxidant and anti-angiogenic effects. These effects are associated with downregulation of pro-inflammatory/pro-angiogenic molecules and upregulation of endothelial nitric oxide synthase (e-NOS) expression/nitric oxide (NO) production. 2. Using the murine sponge model to induce chronic intraperitoneal inflammatory response, we evaluated the inflammatory components, angiogenic and NO production of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 34 publications
1
20
0
1
Order By: Relevance
“…therapeutic sanctions, such as the application of statins, which may have to be precisely adopted to the individual patient background, in order to 1) induce potential beneficial effects and 2) not to provoke undesired reverse effects. In support of this notion it was shown, that statin treatment can be associated with improved survival [21][24] and anti-inflammatory effects in peritoneal dialysis patients [25], [26]. Such potential interrelations will now have to be approached in great detail, whereby several problems, e.g.…”
Section: Discussionmentioning
confidence: 97%
“…therapeutic sanctions, such as the application of statins, which may have to be precisely adopted to the individual patient background, in order to 1) induce potential beneficial effects and 2) not to provoke undesired reverse effects. In support of this notion it was shown, that statin treatment can be associated with improved survival [21][24] and anti-inflammatory effects in peritoneal dialysis patients [25], [26]. Such potential interrelations will now have to be approached in great detail, whereby several problems, e.g.…”
Section: Discussionmentioning
confidence: 97%
“…The intraperitoneal implants were shown to be firmly adhered to surrounding organs (liver and/or intestines), highly vascularized, infiltrated with inflammatory cells, and producing pro-inflammatory and pro-angiogenic cytokines [9,10]. …”
Section: Discussionmentioning
confidence: 99%
“…We have recently reported that implantation of a synthetic matrix in the peritoneal cavity in mice induced a fibroproliferative process whose components, inflammatory cell recruitment, angiogenesis, and extracellular matrix deposition were identified and modulated by various compounds [9,10]. We hypothesized that propolis might be of potential therapeutic value in modulating the components of these lesions in our model.…”
Section: Introductionmentioning
confidence: 99%
“…This method has been modified and used to determine angiogenesis in various experimental models and tissues, including the sponge implant model [6], [12][13]. All implants were individually homogenized (Tekmar TR-10, Cincinnati, OH) in 5 mL of Drabkin reagent (Labtest, São Paulo, Brazil) and centrifuged at 12.000 rpm for 20 min.…”
Section: Methodsmentioning
confidence: 99%